Effect of Supplementing Conjugated Linoleic Acid Producing Bifidobacterial Strains on In vitro Rumen Fermentation Attributes - Jaglan, Neeru; Kumar, Sachin; Choudhury, Prasanta Kumar; Tyagi, Bhawna; Banakar, P. S.; Tyagi, Nitin; Tyagi, Amrish Kumar (Indian Journal of Animal Nutrition, 2020)
The present study was undertaken to evaluate the effects of supplementation of four conjugated linoleic acid (CLA) producing strains of Bifidobacteria isolated from rumen fluid samples of Murrah buffalo (Bubalus bubalis) on ruminal fermentation attributes based on a basal diet having roughage: concentrate in a ratio of 70:30. Results of the study showed that dosing Bifidobacterium strains (109 cells/ml) separately into in vitro incubation tubes neither affect the total gas nor methane (CH4) production after 24 h of incubation. Digestibility parameters showed no significant (P>0.05) changes with respect to in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), or total ammonia-N content of fermentation fluid. However, volatile fatty acid (VFA) concentration was observed to be significantly increased (P